Implementation of Islamic Business Ethics in Conventional Bank BRI Ciamis Branch Office, West Java - Hisam Ahyani; Haris Maiza Putra; Memet Slamet; Muharir Muharir; Andri Nugraha (Departement of Islamic Banking, Faculty of Islamic Economics and Business, The State of Islamic University (UIN) Sultan Maulana Hasanuddin Banten,, 2023)
The purpose of this study is to find out the model and implementation of Islamic business ethics carried out by Bank BRI Ciamis branch office, where in carrying out its business it has put forward the principles of Islamic business ethics in serving consumers. The academic problem that arises is that Bank BRI KC Ciamis is a non-sharia bank, but in service to consumers it prioritizes Islamic business ethical values such as being fair, honest, trustworthy, besides that the majority of Bank BRI KC Ciamis employees are Muslims. The author tries to reveal and dig into this research using descriptive analysis where data sources are obtained through technical interviews, observation and documentation. The findings of this study are that the implementation of business at BRI KC Ciamis bank prioritizes the principles of Islamic business ethics, this can be proven in the 10 behaviors of BRI personnel, including: 1) Excellent Service, 2) employees work 3) effectively and 4) efficiently and 5) prioritizing responsibility, 6) honest, 7) mutual respect, 8) full of innovation, 9) positive attitude and 10) prioritizing trust in consumers. As for added value, namely the brand of BRI bank, namely